Distal kinetic deuterium isotope effect: Phenyl ring deuteration attenuates N-demethylation of Lu AF35700. (15th September 2022) - Gjervig Jensen, Klaus; Tornby Christoffersen, Claus; Graulund Hvenegaard, Mette; Didriksen, Michael; Jørgensen, Morten
Graphical abstract: Abstract: The N -demethylation of zicronapine (7 ) and three of its deuterated analogs 8 – 10 has been studied in human in vitro metabolism systems. While the N -deuterio-methyl analog 8 did not behave differently from the parent in human liver microsomes, a significantly reduced rate of N -demethylation was observed as a consequence of benzene ring deuteration (compound 7 vs. 9 ). Additional deuteration of the N -methyl group, which as mentioned had shown no effect in isolation, further decreased the rate of the N -demethylation reaction (compound 10 vs. 9 ). This paper presents and discusses this unprecedented 'distal kinetic isotope effect' that was observed when incubating the test compounds with human liver microsomes or recombinant human CYP450 liver enzymes.